2021
DOI: 10.3991/ijet.v16i14.23775
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning in Higher Education: A Study of Its Impact on Students’ Performance

Abstract: The key goal of the paper is to study the influence of blended learning on the academic perfor-mance of students of a statistics Bluman course at the University of Ajman. The study was implemented by means of a quasi-experimental design. The sample of the study was 268 students, grouped into two groups: one experimental group (n = 135) that used blended learning; and the other a control group (n = 133) which was educated using the traditional method. The researchers prepared the achievement test as a tool of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The results demonstrated a positive relationship between the effectiveness of BL and SLOs: the more effective that undergraduates perceived BL, the better their SLOs. It supported the results of the previous literature ( Demirkol and Kazu, 2014 ; Alsalhi et al, 2021 ). Moreover, the descriptive analysis provided additional findings for educators when designing and implementing BL for undergraduates.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results demonstrated a positive relationship between the effectiveness of BL and SLOs: the more effective that undergraduates perceived BL, the better their SLOs. It supported the results of the previous literature ( Demirkol and Kazu, 2014 ; Alsalhi et al, 2021 ). Moreover, the descriptive analysis provided additional findings for educators when designing and implementing BL for undergraduates.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“… Kenney and Newcombe (2011) and Demirkol and Kazu (2014) conducted comparisons and found that students in BL environments had higher average scores than those in non-BL environments. Alsalhi et al (2021) utilized a quasi-experimental study at Ajman University ( n = 268) and indicated that the use of BL has a positive effect on students’ academic success in a statistics course. “BL helps to balance a classroom that contains students with different readiness, motivation, and skills to learn.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing consensus that the blending of online learning with face-to-face learning in an integrated and coherent way is an effective approach to teaching and learning in higher education (See for example Ahmed, 2020;Alsalhi et al, 2021;Müller & Mildenberger, 2021;Nayar & Koul, 2020;Zhao 2022). Student feedback has shown that while they value the convenience, flexibility and time efficiencies of online learning (Adams, et al, 2017), they also very much value the face-to-face sessions on campus in which they can engage more directly with their teacher/ instructor and where they are less easily distracted by other digital attractions and devices (see for example Mulyadi et al, 2019;Attard & Holmes, 2020;Lomer & Palmer, 2021).…”
Section: Https://doiorg/1021428/8c225f6e768acd6bmentioning
confidence: 99%
“…In recent years, with the continuous development of Internet technology and educational information technology, the traditional classroom is gradually replaced by blended learning ways which have been widely used. The hybrid learning environment, which combines the advantages of traditional learning methods with that of networked online learning, enables students to obtain learning resources and teachers' help equally anytime and anywhere, thus arousing their initiative, enthusiasm and creativity in learning [1][2][3][4][5][6][7][8][9]. As a product of the information age, networked online learning can capture the needs of students to improve their learning ability in real time, and always pays attention to the phased learning effect of students and the feedback of platform use experience, so as to provide better services for students [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%